Validation of the academic research consortium high bleeding risk criteria in patients undergoing percutaneous coronary intervention: A systematic review and meta-analysis of 10 studies and 67, 862 patients. (15th January 2022) - Silverio, Angelo; Di Maio, Marco; Buccheri, Sergio; De Luca, Giuseppe; Esposito, Luca; Sarno, Giovanna; Vecchione, Carmine; Galasso, Gennaro
Abstract: Background: To assess the performance of the Academic Research Consortium High Bleeding Risk (ARC-HBR) criteria in stratifying the risk of bleeding and ischaemic events after percutaneous coronary intervention (PCI). Methods: MEDLINE, COCHRANE, Web of Sciences, and SCOPUS were searched for studies aimed at validating the ARC-HBR criteria in patients treated with PCI. The primary outcome measure of this meta-analysis was major bleeding. Results: The analysis included 10 studies encompassing 67, 862 patients undergoing PCI; the HBR definition was fulfilled in 44.7% of the cases. The risk of major bleeding was significantly higher in HBR vs. Non-HBR group (RR, 2.56, 95% CI 2.28–2.89). The average C-statistic was 0.64 (95% CI 0.60–0.68), indicating modest discrimination. The risk of intracranial hemorrhage, gastrointestinal bleeding, fatal bleeding, ischaemic stroke, cardiac death and all-cause death was higher in HBR vs. Non-HBR group. Despite a higher incidence of myocardial infarction and stent thrombosis in patients deemed at HBR, the rate of target lesion revascularization was comparable between groups (RR, 1.01, 95% CI 0.88–1.16). The mean effect size for the cumulative incidence of major bleeding exceeded the HBR cut-off value of 4% for all major criteria except one, and for two out of six minor criteria, namely age ≥ 75 years and moderate CKD. Conclusion: The ARC-HBR definition identifies patients at higher risk of major bleeding and other adverse cardiovascular events after PCI. Almost all major criteria, but also two of the minor criteria, were individually associated with rates of major bleeding above 4% thus fulfilling the definition of major HBR criteria. Highlights: The ARC-HBR definition identifies patients at high risk of adverse events. The ARC-HBR definition is associated with a modest discrimination for major bleedings. Higher rate of MI and ST does not correspond to higher rate of TLR in HBR patients. Some minor criteria fulfill the definition of major HBR criteria.